1978
DOI: 10.1021/j100514a010
|View full text |Cite
|
Sign up to set email alerts
|

Structural aspects of solid solutions of enantiomers: the 3-hydroxymethyl- and 3-carboxy-2,2,5,5-tetramethylpyrrolidinyl 1-oxyl systems as examples

Abstract: Most equimolecular mixtures of enantiomers, i.e., tively few (there are ca. 250 inventoried cases1) are conracemates, crystallize as racemic compounds, while reíaglomerates, i.e., cases which permit spontaneous resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 1 publication
0
48
0
Order By: Relevance
“…When a racemic mixture condenses in 3D it may form a racemic compound, in which both enantiomers are present in the same single crystal; a conglomerate, in which the single crystals contain only one enantiomer, but the sample as a whole is racemic; and a solid solution, in which the condensate contains the two enantiomers in a nonordered arrangement [113]. Racemic crystals are by far more common as conglomerate formers, and only a few compounds tend to form solid solutions [113,114], also called a pseudoracemate [115]. Based on only eight examples, Wallach [116] came to the conclusion that racemate crystals tend to pack denser, which would explain their abundance.…”
Section: Racemic Mixturesmentioning
confidence: 99%
“…When a racemic mixture condenses in 3D it may form a racemic compound, in which both enantiomers are present in the same single crystal; a conglomerate, in which the single crystals contain only one enantiomer, but the sample as a whole is racemic; and a solid solution, in which the condensate contains the two enantiomers in a nonordered arrangement [113]. Racemic crystals are by far more common as conglomerate formers, and only a few compounds tend to form solid solutions [113,114], also called a pseudoracemate [115]. Based on only eight examples, Wallach [116] came to the conclusion that racemate crystals tend to pack denser, which would explain their abundance.…”
Section: Racemic Mixturesmentioning
confidence: 99%
“…Lastly, crystalline racemates may be solid solutions, with random dispersion of the two enantiomers throughout the crystal (Jacques et al, 1991). Solid solutions are rare (Huang et al, 2006), but it has been suggested that chiral molecules with a pseudo-element of symmetry are more likely to crystallize as solid solutions (Chion et al, 1978). Similarly, pseudosymmetric diastereomers or enantiomers that are similar in shape to a sufficient extent are more likely to crystallize as solid solutions (Barabas et al, 2000).…”
Section: Two-dimensional Solid Solution Racemate Built Of Infinite Ramentioning
confidence: 99%
“…About 35 years ago, Chion et al. underlined the role of two structural criteria regarding the formation of enantiomeric solid solutions: isosterism (i.e., the building units of opposite chirality are sterically equivalent) and isomorphism (i.e., substitution of one enantiomer by its counterpart in the crystal lattice preserves the main intermolecular interactions of the structure) . Since then, few crystal structures of enantiomeric solid solutions have been reported and thoroughly described .…”
Section: Introductionmentioning
confidence: 99%
“…About 35 years ago, Chion et al underlined the role of two structural criteria regarding the formation of enantiomerics olid solutions:i sosterism( i.e.,t he building units of opposite chirality are sterically equivalent) and isomorphism (i.e.,s ubstitution of one enantiomer by its counterparti nt he crystal lattice preserves the main intermolecular interactions of the structure). [22] Since then,f ew crystal structures of enantiomeric solid solutions have been reported and thoroughly described. [23][24][25][26][27][28][29][30][31][32][33] In some cases,i tc an be observed that isosterism and isomorphism criteria are actually satisfied in relation to ac onformational flexibility of the components, which provides as ufficientd egree of freedom in each enantiomer to mimic the conformation of its counterpart (i.e.,conformational mimicry).…”
Section: Introductionmentioning
confidence: 99%